Diagnosis and treatment of subtalar dislocation of the foot - Bodnya, Оleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Subtalar dislocations of the foot are 0.7 % of all traumatic dislocations. Late elimination of foot dislocation leads to avascular necrosis of the talus (16.7 %) and osteoarthritis of the subtalar and talus-heel-scaphoid joints (13.1–47 %). As a result painfull deformation of the foot develops with long lasting disability, which makes patients invalids. Objective: to evaluate clinical data and to find out the reasons of negative results of treatment of subtalus dislocations. Methods: 17 patients (10 men and 7 women, mean age 37.8 years) were included into the study. There were 15 (88.24 %) internal and 2 (11.76 %) external subtalar dislocations of the foot. In urgency care reduction was done from 2 to 4 hours from the moment of injury in 13 patients, from 5 to 12 hours — in 3, during one day — in 1. Closed subtalar dislocations were eliminated in 10 cases, open — in 7 (3 with open dislocations). American Orthopedic Foot and Ankle Society (AOFAS) scale was used to evaluate functional results. Results: long-term outcomes were studied in 12 (70.6 %) of 17 patients up to 3 years after dislocation. The signs of aseptic necrosis of the talus were not determined on the control radiographs and CT of the foot. The range of motions in the ankle joint was 64.2° ± 5.1°, in the subtalar joint — it was complete and painless. In majority of cases, the most favorable clinical outcomes were observed in internal dislocations than in external ones. According to the scale AOFAS (91.2 ± 3.5) points were obtained. Positive results of treatment were in 66.67 %, satisfactory — 25 %, unsatisfactory — 8.33 %. Conclusions: adequate elimination of dislocations in the subtalar joint in the early period after injury allows to preserve the function of the foot, to reduce the period of rehabilitation and to improve the long-term outcomes of treatment.